2009
DOI: 10.1111/j.1365-2753.2008.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of priority criteria for cataract extraction

Abstract: The priority score we developed identified patients most likely to experience the greatest improvements from cataract extraction. Use of this tool could provide a fairer and more rational way to prioritize patients for cataract extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The four steps included: 1) systematic review to gather available evidence about waiting list problems and prioritization criteria used, 2) compilation of clinical scenarios, 3) expert panel consultations provided with the literature review and the list of scenarios, 4) rating of the scenarios and criteria weighting, carried out in two rounds using a modi ed Delphi method. The researchers then evaluated the reliability of the tool in the context of hip and knee surgeries (21,38,55) as well as its validity for cataract surgeries (21,37,41,56) and these results are detailed in Additional le 4.…”
Section: Spainmentioning
confidence: 99%
See 2 more Smart Citations
“…The four steps included: 1) systematic review to gather available evidence about waiting list problems and prioritization criteria used, 2) compilation of clinical scenarios, 3) expert panel consultations provided with the literature review and the list of scenarios, 4) rating of the scenarios and criteria weighting, carried out in two rounds using a modi ed Delphi method. The researchers then evaluated the reliability of the tool in the context of hip and knee surgeries (21,38,55) as well as its validity for cataract surgeries (21,37,41,56) and these results are detailed in Additional le 4.…”
Section: Spainmentioning
confidence: 99%
“…Inter-rater (21-24, 33, 38, 40, 42, 45, 47, 50, 55, 57, 61, 65) and intra-rater (22,24,33,40,42,47,55,57,61) reliability were evaluated by comparing the priority ratings of two groups of raters (inter) and by comparing priority ratings by the same raters at two different points in time (intra). Face validity (33,38,41,47,52,55) was determined by consultation with stakeholders (e.g. surgeons, clinicians, patients, etc.).…”
Section: Reliability and Validity Of Pptsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Spanish study took aim at strategizing and prioritizing cataract surgery. Gutié rrez et al [15,16] validated a previously developed priority scoring system for timely access of cataract surgery in terms of clinical variables, potential gain in visual acuity, and related quality-of-life factors. They concluded that the use of a scoring tool could provide a more fair and rational way to prioritize patients for cataract extraction and therefore better meet subjective patient perception of waiting for cataract surgery [17].…”
Section: Recent Findingsmentioning
confidence: 99%
“…These tools aim to manage access to care by ranking patients equitably and rigorously in waiting lists based on criteria, so that those with urgent needs receive services before those with less urgent needs [1,4]. Patient prioritization, as a waiting list management strategy, has been studied in a wide variety of clinical health services, such as orthopaedic surgery [5][6][7][8][9][10][11][12], varicose vein surgery [13], cataract surgery [8,[14][15][16][17][18][19][20][21], cardiac surgery [22,23], psychotherapy services [24], and other mental health services [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%